Bond strength of a silicon-based soft liner to three types of denture base materials - Mahmood, Israa Ali; Hasan, Radhwan Himmadi (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Silicon-based soft liners have poor chemical adhesion to denture base resin, as they depend on mechanical interlocking. De-bonding between denture resin and soft liners is a common problem, as it shortens the life of a relined prosthesis. Purpose: The purpose of the study was to assess the tensile bond strength of three types of denture base materials—fabricated by conventional heat curing, computer-aided design/computer-aided manufacture, and three-dimensional printing, or milling—that are bonded to the silicon-based soft liner. The study also aimed to evaluate the effect of surface treatment (acetone; erbium- and chromium-doped yttrium, scandium, gallium, and garnet [Er,Cr:YSGG] laser) of denture base materials on the bonding capability of the soft liner. Methods: A total of 90 specimens were divided into three groups according to the denture base type (conventional, printed, and milled). The 30 specimens in each group were then subdivided into three sub-groups according to the surface treatment (untreated, acetone, and Er,Cr:YSGG), such that each sub-group included 10 specimens. The denture base was bonded to a ready-to-use paste of the silicon-based soft liner. The strength of the tensile bond was tested using a universal testing machine. Data were statistically analyzed using SPSS v.26 software, two-way ANOVA, and Duncan’s test at a significance level of p ≤ 0.05. Results: The milled denture base showed a higher mean tensile bonding strength compared with the conventional and printed denture base materials, at p ≤ 0.05. The surface treatment with Er,Cr:YSGG and the acetone, respectively, showed a higher mean tensile bonding strength value than the untreated group, at p ≤ 0.05. Conclusion: A milled denture is the most favorable denture base material for bonding to a silicon-based soft liner. The use of Er,Cr:YSGG and acetone surface treatment, respectively, enhances the tensile bonding strength.